A temporal window of vulnerability for development of atrial fibrillation with advancing heart failure. (9th January 2014) - Burashnikov, Alexander; Di Diego, José M.; Sicouri, Serge; Doss, Michael Xavier; Sachinidis, Agapios; Barajas‐Martínez, Hector; Hu, Dan; Minoura, Yoshino; Sydney Moise, N.; Kornreich, Bruce G.; Chi, Liguo; Belardinelli, Luiz; et al.
<x xml:space="preserve">Abstract</x> Aims Heart failure (HF) is associated with development of AF and life‐threatening ventricular tachycardia and fibrillation (VT/VF). Vulnerability to development of AF and VT/VF at different stages of HF and the underlying pathophysiological mechanisms are poorly defined. The present study was designed to determine the time‐course of development of electrical and structural remodelling of the atria and ventricles, and their contribution to induction of AF and VT/VF in a canine model of HF. Methods and results Dogs were ventricular tachypaced (VTP) for 2–3 weeks or 5–6 weeks ('early' and 'late' HF, respectively). Electrophysiological studies were performed in isolated atrial and ventricular preparations and correlated with cardiac dimensions and haemodynamic parameters recorded in vivo. Vulnerability to programmed electrical stimulation‐induced AF was greater in early vs. late stages of HF (78% vs. 38%). In contrast, VT/VF was inducible in late but not in early stages of HF (38% vs. 0%). The temporal distinction in atrial and ventricular arrhythmia susceptibility was associated with a much more rapid development of electrical and structural remodelling in atria. Vulnerability to AF developed following moderate electro‐structural remodelling and waned with further progression to severe remodelling, which averted rapid atrial activation. Conclusions A temporal window of vulnerability for AF appears relatively early during development of VTP‐induced HF in dogs, whereas VT/VF vulnerability is observed at more advanced stages of HF. These findings, if confirmed in humans, may have clinical implications with regard to prognosis and approach to therapy of patients with HF.